A benchmark modelling for participation-based tax increment financing. Issue 2 (29th July 2020) - Varli, Yusuf; Ovenc, Gokhan
Abstract : Purpose: This paper aims to present the theoretical and conceptual framework of a new method in public finance called "participation based tax increment financing (P-TIF)" by combining conventional tax increment financing (TIF) within the Sharīʿah-compliance structure. Design/methodology/approach: This study develops a benchmark model for P-TIF, which offers a participative contract between both lender and borrower. With the help of this model, a financing schema in P-TIF is established by incorporating stochastic modelling. Possible implications and alternative options of application are also explored with a discussion of challenges. Findings: The results mainly indicate that P-TIF promises lenders to be a part of increment from tax earnings, in return for a reduced interest rate. They show how a rise in participation of the lender in a given contract lowers the interest rate. Under the base case scenario, the interest rate is reduced to zero when the participation of the lender in tax increment is set at 50%. Practical implications: With the feature of being interest-free, P-TIF can be implied also within the Sharīʿah-compliance framework, thanks to the model it is based on. Additionally, as the model in this paper is parametric, it can be applicable to various cases in Islamic finance. Originality/value: To the best of our knowledge, this is the first paper in the literature in the sense that it provides a conceptual idea and respective model for TIF method within a Sharīʿah-compliance framework.